How to win the battle of ideas in corporate social responsibility: The International Pyramid Model of CSR - Najeb Masoud (International Journal of Corporate Social Responsibility (JCSR), 2017)
This paper reviews the definitions of Corporate Social Responsibility (CSR) as they have evolve over time. It traces the origins of the concept and creates a theoretical framework for international use, thus having the benefit of applicability in both developing as well as developed economies. The models of Carroll and Visser are integrated to produce The International Pyramid Model of CSR, which acknowledges the relative importance of economic, glocal, legal and ethical, and philanthropic aspects of the CSR concept. The primary innovation in the International Pyramid is the development of 'glocal' responsibilities, relating to the environment, socio-cultural matters, technology users, and political rights. Additionally, the International Pyramid condenses Carroll (Business Horizons 34(4):39-48, 1991) pyramid such that the separate legal and ethical responsibilities are merged into one 'legal and ethical' obligation. Furthermore, it offers flexibility by acknowledging that the various responsibilities it embodies can shift up or down the pyramid as priorities change, which is inevitable as businesses and economies differ cross-sectionally, and over time.
Keywords: A1; G30; K4; M2; M14; O10; 650; Corporate Social Responsibility; Carroll's Pyramid Model; Visser’ s Pyramid Model; International Pyramid Model